FAKTOR YANG MEMPENGARUHI AUDIT DELAY (Studi Empiris perusahaan manufaktur sektor industri dasar dan kimia yang Terdaftar di BEI) - Normalita, Vivi; Hendra Ts, Kartika; Suhendro, Suhendro (Universitas Sam Ratulangi, 2020)
This observation aims to test and analyze the influenceof the company size, solvency, auditor opinion, company age, commitee, and Board of Commissioners to the delay. In this research the data used is the secondary data taken from the financial reporting of 62 basic and chemical industry companies listed on the Indonesia Stock Exchange period 2016-2018 using the technique of sampling purposive sampling. The population in this study is the entire basic and chemical Industry company on the Indonesia Stock Exchange period 2016-2018. The data analysis technique used in this study was a double linear regression analysis that previously tested classical assumptions. Annini results show the size of the company's DNA age, which is based on appaudit delay. Sedangkannsolvability, Opiniiauditor, audit committee, the Board of Commissioners there is no influence on the Auditddelay. The benefits of this observation to provide understanding of management to be used as a matter of consideration in making decisions related to the factor of the delay.Â Keywords: Audit Delay, company size, solvency, Opinion Audit, company age, Good Corporate Governance (GCG).Â